Analisis Imbas Defisit Anggaran terhadap Perekonomian di Indonesia - Nuraisah; Amanda, Reydina Pasya; Rambe, Salsabila; Batubara, Maryam (Ikatan Da'i Indonesia, 2024)
A budget deficit is a condition where government expenditure exceeds its income. This can have an impact on various aspects of the economy, both positive and negative. This research aims to analyze the impact of the budget deficit on the economy in Indonesia using the literature study method. Collecting data and information utilizing various sources from reference books, similar previous research results, as well as various journals relating to the problem to be solved. The data analysis technique used is qualitative descriptive analysis. The research results show that a budget deficit can have both positive and negative impacts on the economy in Indonesia. The positive impacts of a budget deficit include: Increasing economic growth, increasing employment opportunities, improving community welfare. However, a budget deficit can also have a negative impact on the economy in Indonesia, including: Increasing inflation, increasing the government debt burden, decreasing the rupiah exchange rate. Based on the research results, it can be concluded that the budget deficit has a complex impact on the economy in Indonesia. The government needs to manage the budget deficit carefully and responsibly in order to maximize the positive impact and minimize the negative impact.